2022
DOI: 10.1155/2022/5097189
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Predictive Sample-to-Cutoff Index for HIV Infection Confirmation Using Elecsys® HIV Combi PT Assay

Abstract: Background. Early and rapid diagnosis is crucial in HIV preventing and treatment. However, the false-positive rate (FPR) by 4-th generation detection assays was high in low-HIV-prevalence regions. Objectives. To analyze the relation between sample-to-cutoff index (COI) and HIV confirmatory results, and to explore a new COI threshold in our own laboratory to predict HIV infection. Methods. We retrospectively analyzed primarily reactive results by Elecsys® HIV combi PT assays and their confirmatory results by we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…All studies include a PPV for the screening test as well as a suggested S/Co ratio for optimal screening test performance. Study N = PPV Mean S/Co ratio of True Positives (Range) Mean S/Co ratio of False Positives (Range) Optimal S/Co ratio (100 % sensitivity maintained unless otherwise stated) Significance of difference in S/Co ratios Xia et al [25] 150,980 28 % 643.5 (9.95 - ≈ 1200) 3.174 (1–23.77) 9.87 (ROC) P < 0.0001 Wang et al [20] 84,702 44 % 458.15 (30.32–1171.33) 3.11 (1–18.55) 24.44 (ROC) P < 0.0001 Kim et al [10] 155,339 31.2 % overall (2.5 % for female samples) 385.97 (7.28–739.98) 2.94 (1.00–34.59) 8.8 (sensitivity 99.36 %) 6.6 (sensitivity 100 %) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies include a PPV for the screening test as well as a suggested S/Co ratio for optimal screening test performance. Study N = PPV Mean S/Co ratio of True Positives (Range) Mean S/Co ratio of False Positives (Range) Optimal S/Co ratio (100 % sensitivity maintained unless otherwise stated) Significance of difference in S/Co ratios Xia et al [25] 150,980 28 % 643.5 (9.95 - ≈ 1200) 3.174 (1–23.77) 9.87 (ROC) P < 0.0001 Wang et al [20] 84,702 44 % 458.15 (30.32–1171.33) 3.11 (1–18.55) 24.44 (ROC) P < 0.0001 Kim et al [10] 155,339 31.2 % overall (2.5 % for female samples) 385.97 (7.28–739.98) 2.94 (1.00–34.59) 8.8 (sensitivity 99.36 %) 6.6 (sensitivity 100 %) …”
Section: Discussionmentioning
confidence: 99%
“…From the other side, Alonso et al stated that 85 % of true positive samples in its study had S/Co above 100 [3] . Xia and colleagues showed that through raising the S/Co ratio threshold to 9.87, the test had the ability to maintain a sensitivity of 100 %, while eliminating 93 % of false positive results [25] . In the pregnancy population realm, a study reported that 100 % of low risk pregnant patients (n = 12) who had reactive ARCHITECT screening tests we ultimately found to be negative for HIV [4] .…”
Section: Discussionmentioning
confidence: 99%
“…This will therefore lead to a risk of delayed medical treatment and increase stress for patients with false-positive results while waiting for the confirmatory results and the patients’ follow-up may fail. Recent studies have demonstrated that false-positive results can be excluded by increasing the signal-to-cutoff (S/CO) positive threshold [ 7 , 10 , 11 ]. In addition to this, rapid diagnostic test(RDT) has become a routine and a part of the standard of care in some HIV testing sites, and it can greatly reduce turnaround time and facilitate rapid linkage to care [ 2 , 12 ].…”
Section: Introductionmentioning
confidence: 99%